Requisitos de autocuidado y su relación con el pie diabético en personas con Diabetes Mellitus - Trujillo, 2015 - Infantes Puelles, Ruth Esther (2015)
Research descriptive - correlational cross-sectional was conducted in people diagnosed with diabetes mellitus attending the Primary Care Center III Metropolitan -Essalud and Aprovida center in 2015, with the aim of determining the relationship between the compliance requirements and the degree of selfcare in the diabetic foot. The sample consisted of 278 adults diagnosed with diabetes mellitus selected according to the inclusion criteria. Scale self-care requirements (ERA), and Rating Scale diabetic foot: To collect data two instruments were used. The results are: 67.6% does not meet the requirements of self care, 52.2% are in category I for grade 0 where standing is at risk without injury, 93.5% of people who are category III, are in grades IV and V and does not meet the requirements of self-care. The conclusion: There is a relationship between compliance requirements and the degree of self diabetic foot less to more fulfillment foot injuries.